Analysis Of The Implementation Of Higher-Order Thinking Skills In Learning Arabic For Speakers of Other Language/ تطبيق وتحليل مهارات التفكير العليا في تعليم اللغة العربية لدى الناطقين بلغة أخرى - Murdhani, Ahmad; al jahrani, Salih Jamman (UIN ANTASARI, 2022)
This study aims to analyze the application of higher-order thinking skill in learning Arabic at Madrasah Aliyah Negeri in Banjarmasin. The results of the study are as follows: The design of learning implementation that contains relevant Higher Order Thinking Skills contains learning indicators from levels C4 to C6. For lesson plan kalam (speaking) and lesson plan kitabah (writing) teachers use operational verb up to level C6 because this is a productive lesson in speaking and writing which requires students to be able, and active in making Arabic conversations and writings. Meanwhile, in the istima' (listening) and qiraah (reading) lesson plans, the teacher only uses operational verb to C3 because this istima' and qiraah learning is receptive in nature, which is different from productive kalam and scriptures. Effective HOTS learning in the implementation of learning includes literacy activities, creativity activities, critical thinking, communication, collaboration. This activity was carried out in Arabic learning activities at the Madrasah Aliyah Negeri in Banjarmasin. In its implementation, teachers also use interactive media such as Whatsapp, Google Meet, Telegram and E-Learning Madrasah. The implementation of the appropriate HOTS evaluation in learning uses an evaluation instrument that is in accordance with the indicators formulated in the lesson plans and the indicators use operational verb from levels C4 to C6.